High-viscosity floor glue, preparation method and composite floor

By adding melamine, starch, lignin, manganese dioxide and other substances to the floor glue, a porous structure and a three-dimensional network structure are formed, which solves the problem of formaldehyde release during the use of urea-formaldehyde resin adhesive and improves the performance of the floor glue. Water resistance and bonding strength, and reduced free formaldehyde content.

CN117801739BActive Publication Date: 2025-01-21CHANGZHOU KAISHENG NEW MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311692232.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-01-21
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

The urea-formaldehyde resin adhesive releases formaldehyde during use, resulting in a decrease in the glue performance. The prior art reduces formaldehyde release by reducing the mass ratio of formaldehyde to urea, but this will affect the glue performance.

Method used

By adding substances such as melamine, starch, lignin and manganese dioxide to the floor glue, a three-dimensional network structure and a porous structure are formed to seal the water-absorbing groups, improve water resistance and bonding strength, and at the same time utilize the photocatalytic effect of manganese dioxide. Adsorbs and decomposes free formaldehyde.

Benefits of technology

It improves the water resistance and bonding strength of floor glue, reduces the content of free formaldehyde, expands the use scope of floor glue, and improves storage stability and use safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801739B_ABST
    Figure CN117801739B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of urea-formaldehyde resin, and more particularly to a high-viscosity floor glue, a preparation method and a composite floor. Wherein, the high-viscosity floor glue comprises the following weight parts of materials: 160-180 parts of formaldehyde, 120-130 parts of urea, 3-4 parts of melamine, 1.5-2.5 parts of additives, 10 parts of water and 1-3 parts of fillers, and the fillers include any one or more of starch, lignin and manganese dioxide. The composite floor comprises an epidermis layer, a substrate layer and a bottom cushion layer arranged sequentially from top to bottom, and the epidermis layer, the substrate layer and the bottom cushion layer are both provided with an adhesive layer in two adjacent layers, and the adhesive layer is composed of the above-mentioned high-viscosity floor glue, and the epidermis layer also includes a UV layer, a PVC wear-resistant layer, a decorative layer and a PVC base material layer arranged sequentially. By adding fillers, the bonding strength of the floor glue is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of urea-formaldehyde resins, and in particular to a high-viscosity floor glue, a preparation method and a composite floor. Background Art

[0002] Urea-formaldehyde resin adhesive is the most widely used synthetic resin adhesive in my country's wood industry. Urea-formaldehyde resin adhesive is usually used as floor adhesive. Urea-formaldehyde resin adhesive has the following advantages: high bonding strength, rapid curing, easy to adjust the appropriate viscosity and concentration, etc., and low price.

[0003] However, urea-formaldehyde resin adhesives have a major drawback: they release formaldehyde during use, and the manufactured products may also continuously release formaldehyde. Therefore, in order to reduce the amount of formaldehyde released in urea-formaldehyde resin adhesives, the molar ratio of formaldehyde to urea is usually reduced. Although this can reduce the amount of free formaldehyde in urea-formaldehyde resin adhesives, it correspondingly reduces the bonding performance of urea-formaldehyde resin adhesives.

[0004] Therefore, we propose a high-viscosity floor glue, a preparation method and a composite floor to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology and to propose a high-viscosity floor glue, a preparation method and a composite floor.

[0006] The purpose of this application is achieved through the following technical solutions:

[0007] In a first aspect, the present application provides a high-viscosity floor adhesive, comprising the following substances in parts by weight: 160-180 parts of formaldehyde, 120-130 parts of urea, 3-4 parts of melamine, 1.5-2.5 parts of additives, 10 parts of water and 1-3 parts of fillers, wherein the fillers include any one or more of starch, lignin and manganese dioxide.

[0008] By adopting the above technical scheme, through the addition of melamine, the ring structure of melamine can be utilized to form a three-dimensional network structure, which can seal the water-absorbing groups in the floor glue, thereby improving the water resistance of the floor glue, and can reduce the free formaldehyde in the floor glue, thereby improving the application range of the floor glue.

[0009] Starch is added to the floor glue base material. Starch has a larger particle size and better bonding effect, which can improve the viscosity of the floor glue. At the same time, the starch material is not easy to penetrate into the gaps in the floor wood, reducing the lack of glue and glue penetration, thereby improving the gluing effect of the floor glue. In addition, because starch can react with the floor glue base material, it reduces the content of hydrophilic groups in the floor glue, thereby improving the water resistance of the floor glue.

[0010] When lignin is added to the floor glue, the lignin does not participate in the synthesis reaction of urea-formaldehyde resin and maintains the structural properties of urea-formaldehyde resin, but can effectively reduce the potential of urea-formaldehyde resin and improve the storage stability of the floor glue.

[0011] Manganese dioxide is added to the floor glue. Manganese dioxide does not change the main functional groups and crystal structure of urea-formaldehyde resin, but the addition of manganese dioxide can promote the polycondensation reaction of formaldehyde and urea, increase the cross-linking degree of urea-formaldehyde resin, stabilize and improve the bonding strength of the floor glue, and reduce the content of free formaldehyde. At the same time, because manganese dioxide has a relatively excellent photocatalytic effect, it can absorb free formaldehyde and decompose it into CO2 and H2O, reducing the free formaldehyde in the floor glue and improving the scope of use of the floor glue.

[0012] Optionally, the manganese dioxide is selected from any one of α-MnO2, β-MnO2, γ-MnO2 or δ-MnO2.

[0013] By adopting the above technical scheme, the crystal structure of manganese dioxide is optimized, α-MnO2 and δ-MnO2 are layered structures, and the fine sheet structures can curl, shrink, and assemble to form larger agglomerates. β-MnO2 and γ-MnO2 are rod-shaped nanostructures. α-MnO2, β-MnO2, γ-MnO2 or δ-MnO2 all have large specific surface areas, oxygen defects, and more surface oxygen, which can further improve the adsorption and degradation effect of manganese dioxide on formaldehyde. Among them, δ-MnO2 has higher surface oxygen, oxygen defects, and a higher average valence of Mn, that is, δ-MnO2 has the best formaldehyde catalytic degradation effect.

[0014] Optionally, the manganese dioxide is loaded on a carrier, and the carrier includes any one or more of sepiolite powder, diatomaceous earth, bentonite and graphite.

[0015] By adopting the above technical scheme, using sepiolite powder, diatomite, bentonite or graphite as a carrier, sepiolite powder, diatomite, bentonite and graphite all have a multi-pore structure and have a better adsorption effect. After the carrier is loaded with manganese dioxide, the large specific surface area of ​​the carrier can fully adsorb free formaldehyde, and formaldehyde is decomposed by manganese dioxide, which can accurately adsorb and decompose free formaldehyde, thereby improving the safety of floor glue. At the same time, the addition of the carrier can reduce the amount of manganese dioxide used and reduce the cost of the floor glue. In addition, the carrier can hinder the agglomeration of manganese dioxide and improve the uniformity of the dispersion of manganese dioxide in the floor glue. The floor glue is made to uniformly obtain the characteristics of low free formaldehyde.

[0016] Optionally, the carrier is a carrier that has not been modified by a modifier, and the modifier includes at least one of sodium hydroxide, hydrochloric acid, and hexadecyltrimethylammonium chloride.

[0017] By adopting the above technical solution, the carrier is modified by sodium hydroxide or hydrochloric acid, so that the surface ash of the carrier can be removed, the surface roughness and specific surface area of ​​the carrier can be increased, the loading capacity of the carrier for manganese dioxide can be increased, and the surface activity of the carrier can be increased, and the adsorption effect of the carrier for formaldehyde can be enhanced. By modifying the carrier with hexadecyltrimethylammonium chloride, active groups are added to the surface of the carrier, the dispersion uniformity of the carrier in the floor glue substrate is improved, and the floor glue obtains a uniform formaldehyde adsorption effect.

[0018] Optionally, the modifier further comprises pectin, and the pectin is selected from any one of beet pectin, potato pectin, citrus pectin and orange peel pectin.

[0019] By adopting the above technical solution, the carrier is modified by using pectin, and the pectin can enhance the adhesion of the carrier surface, enhance the bonding strength between the carrier and manganese dioxide, and make the carrier and manganese dioxide stably cooperate to form a formaldehyde adsorption-degradation system, and stably reduce the content of free formaldehyde in the floor glue. At the same time, the addition of pectin can further enhance the gluing effect of the floor glue. In addition, since pectin has a relatively excellent free radical scavenging effect, it can prolong the storage time of the floor glue.

[0020] Optionally, the manganese dioxide further includes macroporous manganese dioxide.

[0021] By adopting the above technical scheme, macroporous manganese dioxide has a relatively excellent specific surface area and porous structure, so that the macroporous manganese dioxide has excellent surface activity, and the decomposition effect of manganese dioxide on formaldehyde is improved; the porous structure can improve the adsorption effect of manganese dioxide on formaldehyde, so that manganese dioxide itself can absorb and degrade formaldehyde, further reducing the free formaldehyde content in the floor glue.

[0022] Optionally, the macroporous manganese dioxide is loaded with aromatic powder, and the aromatic powder is selected from orange peel powder or tangerine peel powder.

[0023] By adopting the above technical scheme, aromatic powder is added to macroporous manganese dioxide. Firstly, the aromatic powder is not easy to participate in the synthesis reaction of urea-formaldehyde resin, so the bonding effect of the floor glue is maintained; secondly, the presence of the aromatic powder can give the floor glue an aromatic smell, so as to improve the use effect of the floor glue; in addition, the presence of pectin, cellulose, hemicellulose and other substances in the aromatic powder can not only further enhance the bonding effect between the macroporous manganese dioxide and the carrier, but also play an adsorption and complexation role, so as to enhance the adsorption effect of the macroporous manganese dioxide on formaldehyde.

[0024] Optionally, the preparation method of the aromatic powder includes the following steps: taking orange peel or tangerine peel, drying at a constant temperature, crushing, and sieving to obtain a powder raw material; immersing the powder raw material in isopropanol, letting it stand, washing with water, filtering with suction, retaining solid matter, and drying to obtain an intermediate; immersing the intermediate in 2% by mass sodium hydroxide, letting it stand, washing with water, filtering with suction, retaining solid matter, and drying to obtain an aromatic powder.

[0025] By adopting the above technical solution, the aromatic powder is modified and modified by isopropyl alcohol and sodium hydroxide, which can improve the adsorption effect of the aromatic powder, thereby reducing the content of free formaldehyde in the floor glue. At the same time, the modified aromatic powder can combine with formaldehyde to obtain a rough, loose, porous, and uneven surface, and obtain a heavy metal adsorption effect, that is, the modified aromatic powder can effectively adsorb and fix free formaldehyde, further reducing the free formaldehyde in the floor glue.

[0026] In a second aspect, the present application provides a method for preparing a high-viscosity floor adhesive, comprising the following steps:

[0027] S1, raw material mixing: formaldehyde, urea, melamine, additives, fillers and water are weighed respectively by weight, and urea is divided into four parts V1, V2, V3 and V4, formaldehyde is taken, the temperature is increased, alkali is adjusted to a solution pH of 8.5-8.8, urea V1 and melamine are added, the temperature is increased and kept warm, and an intermediate solution is obtained;

[0028] S2, polycondensation: adding acid solution to the intermediate solution, adjusting the pH to 5.0-5.2, and heat-preserving polycondensation to obtain a polycondensation product;

[0029] S3, preparation of adhesive solution: add auxiliary agent I, filler and urea V2 to the polycondensation product, adjust the pH to 6.2-6.5, add auxiliary agent II, adjust the pH to 7.0-7.5 with alkaline solution, keep the reaction warm, cool down, add urea V4, adjust the pH to 7.5-8.0, and prepare the floor adhesive.

[0030] By adopting the above technical scheme, adding urea in four batches in the synthesis process can effectively adjust the molecular ratio in the condensation reaction stage and improve the degree of polycondensation. In particular, the third and fourth additions of urea can effectively capture the formaldehyde that has not been fully reacted in the reaction solution, thereby reducing the free formaldehyde in the modified urea-formaldehyde resin.

[0031] In the third aspect, the present application provides a composite floor, comprising an epidermis layer, a substrate layer, and a bottom cushion layer arranged in sequence from top to bottom, wherein the epidermis layer, the substrate layer, and the two adjacent layers of the bottom cushion layer each have an adhesive layer, and the adhesive layer is composed of the above-mentioned high-viscosity floor glue, and the epidermis layer also includes a UV layer, a PVC wear-resistant layer, a decorative layer, and a PVC base material layer arranged in sequence.

[0032] In summary, this application has the following technical effects:

[0033] 1. The ring structure of melamine is used to form a three-dimensional network structure in the floor glue, which seals the water-absorbing groups in the floor glue, improves the water resistance of the floor glue, and reduces the content of free formaldehyde.

[0034] Due to the large particle size and good adhesion of starch, the viscosity of floor glue can be improved. At the same time, starch material is not easy to penetrate into the gaps of floor wood, reducing the phenomenon of glue deficiency and glue penetration. And because starch can react with the floor glue base material, it reduces the content of hydrophilic groups in the floor glue, thereby improving the water resistance of the floor glue.

[0035] Since lignin does not participate in the synthesis reaction of urea-formaldehyde resin, it maintains the structural properties of urea-formaldehyde resin, but can effectively reduce the potential of urea-formaldehyde resin and improve the storage stability of floor glue.

[0036] Although manganese dioxide does not change the main functional groups and crystal structure of urea-formaldehyde resin, the addition of manganese dioxide can promote the polycondensation reaction of formaldehyde and urea, increase the cross-linking degree of urea-formaldehyde resin, stabilize and improve the bonding strength of floor glue, and reduce the content of free formaldehyde. At the same time, because manganese dioxide has a relatively excellent photocatalytic effect, it can absorb free formaldehyde and decompose it into CO2 and H2O, reducing the free formaldehyde in the floor glue and improving the application range of the floor glue.

[0037] 2. Use sepiolite powder, diatomite, bentonite or graphite as carriers. Sepiolite powder, diatomite, bentonite and graphite all have multiple pore structures and have better adsorption effects. After the carrier is loaded with manganese dioxide, the large specific surface area of ​​the carrier can fully adsorb free formaldehyde, and formaldehyde can be decomposed by manganese dioxide. It can accurately adsorb and decompose free formaldehyde, and improve the safety of floor glue. At the same time, the addition of the carrier can reduce the amount of manganese dioxide used and reduce the cost of floor glue. In addition, the carrier can hinder the agglomeration of manganese dioxide and improve the uniformity of the dispersion of manganese dioxide in the floor glue. Make the floor glue uniformly obtain the characteristics of low free formaldehyde.

[0038] 3. Use pectin to modify the carrier. Pectin can enhance the adhesion of the carrier surface and the bonding strength between the carrier and manganese dioxide, so that the carrier and manganese dioxide can be stably matched to form a formaldehyde adsorption-degradation system, which can stably reduce the content of free formaldehyde in the floor glue. At the same time, the addition of pectin can further enhance the bonding effect of the floor glue. In addition, since pectin has a relatively excellent free radical scavenging effect, it can extend the storage time of the floor glue.

[0039] 4. Modify the aromatic powder. Using isopropyl alcohol and sodium hydroxide to modify the aromatic powder can improve the adsorption effect of the aromatic powder, thereby reducing the content of free formaldehyde in the floor glue. At the same time, the modified aromatic powder can combine with formaldehyde to obtain a rough, loose, porous, and uneven surface, and obtain a heavy metal adsorption effect, that is, the modified aromatic powder can effectively adsorb and fix free formaldehyde, further reducing the free formaldehyde in the floor glue. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic diagram of a composite floor in this application.

[0041] Explanation of the accompanying drawings: 1. epidermis layer; 11. UV layer; 12. PVC wear-resistant layer; 13. decorative layer; 14. PVC base material layer; 2. base material layer; 3. bottom cushion layer. DETAILED DESCRIPTION

[0042] The present invention will be further explained below in conjunction with specific embodiments.

[0043] Preparation Example

[0044] Filler Preparation Example

[0045] Preparation Example 1-4

[0046] Starch, lignin and manganese dioxide are taken separately, and the specific masses are shown in Table 1, and mixed to prepare fillers 1-4. Among them, lignin is sodium lignin sulfonate, and manganese dioxide is α-MnO2.

[0047] Table 1 Filler composition of Preparation Examples 1-4

[0048] Weight / kg Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 starch 20 - - 15 Sodium lignin sulfonate - 20 - 3 Manganese dioxide - - 20 2

[0049] Preparation Example 5

[0050] The difference from Preparation Example 3 is that filler 5 is prepared by using δ-MnO2 in the crystal form to replace the manganese dioxide in Preparation Example 3.

[0051] Preparation Example 6-9

[0052] The difference from Preparation Example 3 is:

[0053] Sepiolite powder, diatomaceous earth, bentonite and graphite were used as carriers respectively, 20 kg of manganese dioxide was dispersed in water to obtain a mixed solution, 5 kg of the carrier was dispersed in the mixed solution, stirred, filtered and dried to obtain carrier-loaded manganese dioxide 1-4, and equal masses of carrier-loaded manganese dioxide 1-4 were used to replace the manganese dioxide in Preparation Example 3 to prepare fillers 6-9.

[0054] Preparation Example 10

[0055] The difference from Preparation Example 8 is:

[0056] Take 5 kg of bentonite and immerse it in 5% hydrochloric acid, raise the temperature to 60°C, keep the temperature for 6 hours, filter, retain the solid, and dry to obtain acid-modified bentonite. Use the acid-modified bentonite to replace the bentonite in Preparation Example 8 to prepare filler 10.

[0057] Preparation Example 11

[0058] The difference from Preparation Example 8 is:

[0059] Filler 11 was prepared by using an equal mass of modified bentonite as a filler to replace the bentonite in Preparation Example 8.

[0060] Preparation method of modified bentonite: 5 kg of the acid-modified bentonite prepared in Preparation Example 10 is immersed in hexadecyltrimethylammonium chloride, filtered, the solid matter is retained, and dried to obtain modified bentonite.

[0061] Preparation Example 12

[0062] The difference from Preparation Example 8 is:

[0063] Take 1 kg of orange peel pectin and dissolve it in a 5% hydrochloric acid solution to obtain a pectin solution. Impregnate bentonite in the pectin solution, filter, retain the solid matter, and dry to obtain pectin-modified bentonite. Use the pectin-modified bentonite to replace the bentonite in Preparation Example 8 to prepare filler 12.

[0064] Preparation method of orange peel pectin: take orange peel, wash, cut into pieces, soak in water at 95°C for 5 minutes, dry to constant weight, grind, sieve to obtain orange peel powder. Soak tangerine peel powder in hydrochloric acid solution with a pH of 2.5, stir evenly, extract with ultrasonic microwave synergistic extraction at 600W for 30 minutes to obtain extract, centrifuge, retain supernatant, add ethanol, stand overnight, centrifuge, retain solid matter, wash with alcohol, rotary evaporate, freeze-dry, and obtain orange peel pectin.

[0065] Preparation Example 13

[0066] The difference from Preparation Example 3 is:

[0067] The manganese dioxide includes equal masses of α-MnO2 and macroporous manganese dioxide, which are mixed to obtain mixed manganese dioxide to replace the manganese dioxide in Preparation Example 3 to prepare filler 13.

[0068] Among them, the specific surface area of ​​macroporous manganese dioxide is 95.685m 2 / g, pore diameter is 6.889nm, pore volume is 0.167cm 2 / g.

[0069] Preparation Example 14

[0070] The difference from Preparation Example 13 is:

[0071] Take 1 kg of orange peel powder and mix it with 10 kg of macroporous manganese dioxide, sieve it, and obtain macroporous manganese dioxide loaded with aromatic powder. Take an equal mass of macroporous manganese dioxide loaded with aromatic powder to replace the macroporous manganese dioxide in Preparation Example 13 to prepare filler 14.

[0072] Preparation Example 15

[0073] The preparation of aromatic powder comprises the following steps: taking orange peel, drying at a constant temperature, crushing, and sieving to obtain a powder raw material; immersing the powder raw material in 20% by mass isopropanol, standing for 24 hours, washing with water until colorless, filtering with suction, retaining solids, and drying for 24 hours to obtain an intermediate; immersing the intermediate in 2% by mass sodium hydroxide, standing for 24 hours, washing with water until the pH value is neutral, filtering with suction, retaining solids, and drying for 24 hours to obtain aromatic powder.

[0074] Example

[0075] Examples 1-3

[0076] The present application provides a high-viscosity floor adhesive, including the following substances: formaldehyde, urea, melamine, additives, and fillers, and the specific masses are shown in Table 2. Among them, the additives include additives I and additives II, additive I is a water-resistant agent, the water-resistant agent is resorcinol, and additive II is a tackifier, and the tackifier is polyvinyl alcohol.

[0077] The present application also provides a method for preparing a high-viscosity floor adhesive, comprising the following steps:

[0078] S1. Mixing raw materials: weigh formaldehyde, urea, melamine, additives, fillers and water respectively by weight, and divide urea into four parts: V1, V2, V3 and V4; take formaldehyde, heat to 35°C, adjust the solution pH to 8.5-8.8 with alkali, add urea V1, heat to control the temperature, add melamine at 40°C (add before 70°C), heat to 85°C for 30-40 minutes, and keep warm at 85-88°C to obtain an intermediate solution;

[0079] S2, polycondensation: add water to the intermediate solution for 5 minutes, add acid at a temperature of 80-83°C, adjust the pH to 5.0-5.2 for 20-30 minutes, and heat at 90-92°C for polycondensation for 60-90 minutes to obtain a polycondensation product with a material viscosity of 19-20s;

[0080] S3, preparation of adhesive solution: add auxiliary agent I, filler and urea V2 to the condensation product, adjust the pH to 6.2-6.5, keep warm at 80-83℃ for 30min, and adjust the viscosity of the material to 19"5-20"5; add auxiliary agent II, adjust the pH to 7.0-7.5 with alkali solution, keep warm at 70-75℃ for 15min, cool down, adjust the pH to 7.5-8.0 at 42℃, and prepare the floor adhesive.

[0081] The present application also provides a composite floor, comprising an epidermis layer, a substrate layer, and a bottom cushion layer arranged in sequence from top to bottom, wherein the epidermis layer, the substrate layer, and the two adjacent layers of the bottom cushion layer each have an adhesive layer, and the adhesive layer is composed of the above-mentioned high-viscosity floor glue, and the epidermis layer also includes a UV layer, a PVC wear-resistant layer, a decorative layer, and a PVC base material layer arranged in sequence.

[0082] Table 2 Composition of floor adhesive in Examples 1-3

[0083]

[0084] Embodiment 4-16

[0085] The difference from Example 2 is that fillers 2-14 of equal mass are used to replace filler 1 in Example 2 to prepare floor glue and composite floor.

[0086] Comparative Example

[0087] Comparative Example 1

[0088] The difference from Example 2 is that in this comparative example, no filler is added to the floor glue to prepare the floor glue and the composite floor.

[0089] Comparative Example 2

[0090] The difference from Example 2 is that in this comparative example, silicon dioxide is used as filler to prepare floor glue and composite floor.

[0091] Performance Testing

[0092] 1. Adhesive performance test

[0093] The bonding properties of the floor adhesives in Examples 1-16 and Comparative Examples 1-2 were tested in accordance with GB / T17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels".

[0094] 2. Formaldehyde emission test

[0095] The formaldehyde emission of the floor glue in Examples 1-16 and Comparative Examples 1-2 was tested according to GB / T18580-2001.

[0096] Table 3 Floor glue performance test table

[0097]

[0098]

[0099] The floor glue prepared in Example 14 and Example 16 has a certain aromatic smell.

[0100] By referring to the performance test comparison in Table 3, we can find that:

[0101] 1. By comparing Examples 1-3, Examples 4-6 and Comparative Examples 1-2, it can be found that the bonding strength of the floor glue prepared in Examples 1-3 is improved and the formaldehyde emission is reduced. This shows that the ring structure of melamine is used in the present application to form a three-dimensional network structure, which closes the water-absorbing groups in the floor glue, thereby improving the water resistance of the floor glue, reducing the free formaldehyde in the floor glue, and improving the scope of use of the floor glue. Starch materials can improve the bonding effect of the floor glue, reduce the content of hydrophilic groups in the floor glue, and improve the water resistance of the floor glue. Lignin can reduce the potential of urea-formaldehyde resin and improve the storage stability of the floor glue. The addition of manganese dioxide can promote the polycondensation reaction of formaldehyde and urea, increase the crosslinking degree of urea-formaldehyde resin, improve the bonding strength of the floor glue, and reduce the content of free formaldehyde. At the same time, it can adsorb free formaldehyde and decompose it into CO2 and H2O, reducing the free formaldehyde in the floor glue.

[0102] 2. By comparing Example 7 with Example 2, it can be found that the bonding strength of the floor glue prepared in Example 7 is improved and the formaldehyde emission is reduced, which indicates that δ-MnO2 in the present application has higher surface oxygen, oxygen defects and higher average Mn valence, that is, δ-MnO2 has the best formaldehyde catalytic degradation effect.

[0103] 3. By comparing Examples 8-11 with Example 2, it can be found that the bonding strength of the floor glue prepared in Examples 8-11 is improved and the formaldehyde emission is reduced. This shows that in this application, sepiolite powder, diatomaceous earth, bentonite or graphite are used as carriers. Sepiolite powder, diatomaceous earth, bentonite and graphite all have multiple pore structures and have better adsorption effects. After the carrier is loaded with manganese dioxide, the large specific surface area of ​​the carrier can fully adsorb free formaldehyde, and formaldehyde can be decomposed by manganese dioxide, which can accurately adsorb and decompose free formaldehyde, thereby improving the safety of the floor glue. At the same time, the addition of the carrier can reduce the amount of manganese dioxide used and reduce the cost of the floor glue. In addition, the carrier can hinder the agglomeration of manganese dioxide and improve the uniformity of the dispersion of manganese dioxide in the floor glue.

[0104] 4. By comparing Examples 12-13 with Example 2, it can be found that the bonding strength of the floor glue prepared in Examples 12-13 is improved and the formaldehyde emission is reduced, which indicates that the use of hydrochloric acid to modify bentonite in this application can remove the surface ash of bentonite, increase the surface roughness and specific surface area of ​​bentonite, increase the loading capacity of bentonite for manganese dioxide, and increase the surface activity of bentonite, thereby enhancing the adsorption effect of bentonite on formaldehyde. By modifying bentonite with hexadecyltrimethylammonium chloride, active groups are added to the surface of bentonite, and the uniformity of the dispersion of bentonite in the floor glue substrate is improved; at the same time, starch can also be combined with bentonite to further promote the participation of formaldehyde in polycondensation and reduce the amount of free formaldehyde.

[0105] 5. By comparing Example 14 with Example 2, it can be found that the bonding strength of the floor glue prepared in Example 14 is improved and the formaldehyde emission is reduced. This shows that in the present application, pectin is used to modify the carrier. Pectin can enhance the adhesion of the carrier surface and the bonding strength between the carrier and manganese dioxide, so that the carrier and manganese dioxide can stably cooperate to form a formaldehyde adsorption-degradation system, thereby stably reducing the content of free formaldehyde in the floor glue.

[0106] 6. By comparing Examples 15-16 with Example 2, it can be found that the bonding strength of the floor glue prepared in Examples 16-17 is improved and the formaldehyde emission is reduced, which means that in the present application, aromatic powder is added to the macroporous manganese dioxide. First, the aromatic powder is not easy to participate in the synthesis reaction of urea-formaldehyde resin, thereby maintaining the bonding effect of the floor glue; secondly, the presence of the aromatic powder can give the floor glue an aromatic smell and improve the use effect of the floor glue; in addition, the presence of pectin, cellulose, hemicellulose and other substances in the aromatic powder can not only further enhance the bonding effect between the macroporous manganese dioxide and the carrier, but also play an adsorption and complexation role, thereby enhancing the adsorption effect of the macroporous manganese dioxide on formaldehyde.

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-viscosity floor adhesive, characterized in that: The invention comprises the following materials in parts by weight: 160-180 parts of formaldehyde, 120-130 parts of urea, 3-4 parts of melamine, 1.5-2.5 parts of additives, 10 parts of water and 10-20 parts of fillers, wherein the fillers include any one or more of starch, lignin and manganese dioxide; The manganese dioxide is selected from any one of α-MnO2, β-MnO2, γ-MnO2 or δ-MnO2; The manganese dioxide is loaded on a carrier, and the carrier includes any one or more of sepiolite powder, diatomaceous earth, bentonite and graphite; The carrier is a carrier modified by a modifier, and the modifier includes at least one of sodium hydroxide, hydrochloric acid, and hexadecyltrimethylammonium chloride; The modifier further comprises pectin, and the pectin is selected from any one of beet pectin, potato pectin, citrus pectin and orange peel pectin.

2. The high-viscosity floor adhesive according to claim 1, characterized in that: The manganese dioxide also includes macroporous manganese dioxide.

3. The high-viscosity floor adhesive according to claim 2, characterized in that: The macroporous manganese dioxide is loaded with aromatic powder, and the aromatic powder is selected from orange peel powder or tangerine peel powder.

4. The high-viscosity floor adhesive according to claim 3, characterized in that: The preparation method of the aromatic powder comprises the following steps: taking orange peel or tangerine peel, drying at a constant temperature, crushing, and sieving to obtain a powder raw material; immersing the powder raw material in isopropanol, standing, washing, filtering, retaining solids, and drying to obtain an intermediate; immersing the intermediate in sodium hydroxide with a mass fraction of 2%, standing, washing, filtering, retaining solids, and drying to obtain the aromatic powder.

5. The method for preparing a high-viscosity floor adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, raw material mixing: formaldehyde, urea, melamine, additives, fillers and water are weighed respectively by weight, and urea is divided into four parts V1, V2, V3 and V4, formaldehyde is taken, the temperature is increased, alkali is adjusted to a solution pH of 8.5-8.8, urea V1 and melamine are added, the temperature is increased and kept warm, and an intermediate solution is obtained; S2, polycondensation: adding acid solution to the intermediate solution, adjusting the pH to 5.0-5.2, and heat-preserving polycondensation to obtain a polycondensation product; S3, preparation of adhesive solution: add auxiliary agent I, filler and urea V2 to the polycondensation product, adjust the pH to 6.2-6.5, add auxiliary agent II, adjust the pH to 7.0-7.5 with alkaline solution, keep the reaction warm, cool down, add urea V4, adjust the pH to 7.5-8.0, and prepare the floor adhesive.

6. A composite floor, characterized in that: The invention comprises a surface layer, a base material layer and a bottom cushion layer which are arranged in sequence from top to bottom, wherein the surface layer, the base material layer and the bottom cushion layer each have an adhesive layer in two adjacent layers, and the adhesive layer is composed of the high-viscosity floor glue according to any one of claims 1 to 4, and the surface layer also comprises a UV layer, a PVC wear-resistant layer, a decorative layer and a PVC base material layer which are arranged in sequence.

Citation Information

Patent Citations

  • Formaldehyde-inhibiting composite clay adhesive filler

    CN102344765A

  • Urea formaldehyde resin adhesive for wood composite floor boards

    CN105086896A

  • Hard floor and preparation method thereof

    CN106957501A

  • High-performance adhesive for glued board

    CN107699192A

  • Diatomite coating for catalytically decomposing formaldehyde and preparation method thereof

    CN108912752A